Pematuhan industri pembuatan terhadap peraturan alam sekitar di Utara Semenanjung Malaysia - Nawawi, Mohd Nasir; Ali, Jamal; Lim, Hock Eam (Universiti Kebangsaan Malaysia, 2013)
Water pollution by industrial effluentis one of the major environmental problems affecting Malaysia in term of environmental quality. Although the country has implemented a range of anti-pollution legislation, the problem has not been resolved and companies continue to pollute on a large scale.This makes it important to understand why current environmental legislation is not working and what must be done to improve the situation. Studies on compliance with environmental regulations are not only important for protecting the environment and ecosystem, but also provide credibility to enforcement agencies about its regulatory programs.An econometric model was used to estimate the violation decision of company owners and managers of food, textile and paper industry in Penang, Kedah and Perlis.The study finds that, although the legislation has been successful in raising environmental awareness among businesses, it has been less successful at reducing effluent pollution.The study shows that many company owners and managers have an adequate knowledge of environmental protection.It is also clear that companies do not consider environmental protection as a top priority.Overall, cost of effluent treatment and the probability of detection can influence compliance behaviour of companies with regard to environmental regulations.The study makes a number of suggestions for improving the effectiveness of environmental legislations.Recommendations include increasing tax incentives for effluent treatment equipment and frequency in enforcement activity to motivate business firms to comply with environmental regulations.